Symbiosis Islands - Ramsay, Joshua; Hynes, M.; Sullivan, J.; Ronson, C. (Elsevier, 2017)
A symbiosis island is a genomic island that confers upon the bacterium carrying it the ability to form a mutualistic relationship with a eukaryotic host. The symbiosis island of Mesorhizobium loti strain R7A (ICEMlSymR7A) is a 501.8-kb chromosomally integrated element that is able to excise and transfer by conjugation to nonsymbiotic mesorhizobia in the environment. The recipients are converted to symbionts able to nodulate and fix nitrogen with Lotus species. ICEMlSymR7A is a member of an emerging class of acquired genetic elements termed “integrative and conjugative elements” (ICEs) that contribute to the diversification and adaptation of bacteria to environmental niches. A regulatory cascade involving bacterial cell–cell communication (quorum sensing), protein antiactivation and programmed ribosomal frameshifting control the process of ICEMlSymR7A excision from the chromosome and transfer to non-symbiotic bacteria.